2013
DOI: 10.1126/scitranslmed.3006898
|View full text |Cite
|
Sign up to set email alerts
|

Phytosterols Promote Liver Injury and Kupffer Cell Activation in Parenteral Nutrition–Associated Liver Disease

Abstract: Parenteral nutrition–associated liver disease (PNALD) is a serious complication of PN in infants who do not tolerate enteral feedings, especially those with acquired or congenital intestinal diseases. Yet, the mechanisms underlying PNALD are poorly understood. It has been suggested that a component of soy oil (SO) lipid emulsions in PN solutions, such as plant sterols (phytosterols), may be responsible for PNALD, and that use of fish oil (FO)–based lipid emulsions may be protective. We used a mouse model of PN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
274
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 189 publications
(295 citation statements)
references
References 47 publications
17
274
1
3
Order By: Relevance
“…Some research suggests that phytosterols, a component of soy lipid emulsions, can suppress bile acid synthesis and impact bile acid efflux target genes in the liver through inhibition of the nuclear hormone receptor, farnesoid X receptor. A recent report by El Kasmi et al (8) suggests that phytosterols taken up by Kupffer cells mediate an inflammation-induced injury to hepatocytes. However, our recent study in PN-fed piglets showed that a lipid emulsion blend of soy, medium-chain triglycerides (MCTs), olive oil, and fish oil, which contains less than one-half the total phytosterol content as soy-lipid emulsions [207 mg/dl vs. 439 mg/dl (9)], also protects against PNALD (7).…”
Section: Nutritional Support and Study Designmentioning
confidence: 99%
“…Some research suggests that phytosterols, a component of soy lipid emulsions, can suppress bile acid synthesis and impact bile acid efflux target genes in the liver through inhibition of the nuclear hormone receptor, farnesoid X receptor. A recent report by El Kasmi et al (8) suggests that phytosterols taken up by Kupffer cells mediate an inflammation-induced injury to hepatocytes. However, our recent study in PN-fed piglets showed that a lipid emulsion blend of soy, medium-chain triglycerides (MCTs), olive oil, and fish oil, which contains less than one-half the total phytosterol content as soy-lipid emulsions [207 mg/dl vs. 439 mg/dl (9)], also protects against PNALD (7).…”
Section: Nutritional Support and Study Designmentioning
confidence: 99%
“…9,10 In mice, the combination of PN and lipopolysaccharide translocation induced by intestinal injury synergistically activates Kupffer cell expression of proinflammatory cytokines and fibrogenic growth factors. 4,5 In accordance with experimental studies, PN-dependent children with IF display an overabundance of lipopolysaccharideproducing Proteobacteria in their intestinal microbiota in association with histologic liver injury, intestinal inflammation, and increased levels of serum proinflammatory cytokines. 11 Liver fibrosis is observed with increasing frequency after extensive distal small intestinal resection in children 6,8 and even without a history of PN administration in pigs, 12 supporting an essential role of disturbed intestinal homeostasis in the pathogenesis of IFALD.…”
mentioning
confidence: 81%
“…Control serum samples were obtained from healthy, age-matched (9.7 years [5. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16], P = .693), day-operative patients (n = 74) without metabolic, gastrointestinal, or hepatobiliary disease. Age-matched (15.0 years [8.1-17], P = .141) transplant donor livers (n = 22) were used as controls for liver immunohistochemistry.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it was shown that mice with intestinal injury that received soy oil-based parenteral nutrition containing phytosterols exhibited an exacerbated decrease in mMrp2 mRNA levels. The phytosterol stigmasterol was at least partially involved and associated with increased levels of interleukin IL-mRNA and reduced levels of FXR mRNA in liver [39].…”
Section: Transcriptional Regulationmentioning
confidence: 99%
“…Intestinal injury caused by indomethacin can increase endotoxin levels in portal blood [3 ], which in turn induces several immune responses and oxidative stress, as shown by the reduced levels of hepatic GSH and increased levels of nitric oxide NO and nitrosothiols in portal blood [35]. In this regard, El Kasmi et al demonstrated that dextran sulfate sodium-induced intestinal injury also downregulates hepatic mMrp2 expression in mice liver and that the intestinal microbiota and TLR Toll-like receptor are involved in this efect [39]. In addition, it was shown that mice with intestinal injury that received soy oil-based parenteral nutrition containing phytosterols exhibited an exacerbated decrease in mMrp2 mRNA levels.…”
Section: Transcriptional Regulationmentioning
confidence: 99%